10 Current Utilisation of High-Sensitivity Troponin; Does it Improve Our Accuracy in Diagnosing Acute Myocardial Infarction?. (6th June 2015) - Davies, Thomas; Silva, Kalpa De; Haslam, Daniel; Fluck, David; Williams, Mark; Jacques, Adam; Mahmoudi, Michael
Abstract : Introduction: High sensitivity troponin assays (Hs-Tn) are part of the diagnostic criteria for identifying myocardial infarction, in the presence of ischaemic chest pain, with or without ECG changes. However, the increased sensitivity of the new generation HS-Tn assays has come at the expense of a marked reduction in specificity, which is further confounded when sampled inappropriately in the absence of clinical features suggestive of an acute coronary syndrome (ACS). We audited the utilisation of HS-Tn in both the emergency and acute medical departments at our institution. Methods: A retrospective observational audit was performed before and after formal education was delivered to the hospital regarding use of HS-TnI, between October 2013 and July 2014. The audit was assessed against current European Society of Cardiology guidelines in the use of HS-Tn in diagnosing ACS. The main parameters assessed were presence of symptoms or ECG findings in keeping with an ischaemic-episode and the concordance of the initial diagnosis with the subsequent cardiologist-guided diagnosis. Results: Ninety-six consecutive patients were sampled in the two audit cycles (50 in the initial cohort and 46 in the re-audit. All patients had HS-TnI assayed on admission and initial treatment with anti-platelet and anti-thrombotic therapy commenced. 46% (n = 23/50) (Figure 1 ) vs. 67% (n = 31/46) sampled in the presence of chest pain +/- ECG changes. 8% (n = 4/50) vs. 11% (n = 5/46) were treated for an ACS following cardiology review, with 92% (n = 46/50) vs. 89% (n = 41/46), having no evidence of ACS. 52% (n = 26/46) (Figure 2 ) vs. 34% (14/41) of the cohorts had an elevated HS-TnI (>0.04 mcg/L), attributable to concurrent sepsis, renal dysfunction or tachy-arrhythmias. Conclusion: HS-Tn is frequently performed in the absence of clinical features or clinical suspicion of an ACS, reducing the specificity of the test. There are important clinical and financial implications with the inappropriate use of Troponin assays outside of the context of a clinical suspicion of an ACS. Improved education and adherence to guidelines is paramount in improving clinical and diagnostic accuracy of this cardiac biomarker in identifying ACS.